2021
DOI: 10.1038/s41416-021-01650-0
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of intermittent vs continuous energy restriction during chemotherapy for early breast cancer

Abstract: Background Excess adiposity at diagnosis and weight gain during chemotherapy is associated with tumour recurrence and chemotherapy toxicity. We assessed the efficacy of intermittent energy restriction (IER) vs continuous energy restriction (CER) for weight control and toxicity reduction during chemotherapy. Methods One hundred and seventy-two women were randomised to follow IER or CER throughout adjuvant/neoadjuvant chemotherapy. Primary endpoints were wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…Our results are consistent with the available literature. TRF showed similar results to the work of Kalam et al [ 39 ], with a high degree of adherence and decrease in weight, and Harvie et al [ 41 ], where IF had a bigger drop in weight compared with CR. However, differences in the mean changes may be explained by the fact that they used another approach of IF which focuses on the amount of calories consumed.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results are consistent with the available literature. TRF showed similar results to the work of Kalam et al [ 39 ], with a high degree of adherence and decrease in weight, and Harvie et al [ 41 ], where IF had a bigger drop in weight compared with CR. However, differences in the mean changes may be explained by the fact that they used another approach of IF which focuses on the amount of calories consumed.…”
Section: Discussionsupporting
confidence: 84%
“…A large RCT with 187 patients from 2022 [ 41 ] compared intermittent and continous energy restriction during chemotherapy for early breast cancer cases. This study concluded that an intermittent restriction approach had a bigger weight reduction than a continuous restriction when adjusted for total body water.…”
Section: Introductionmentioning
confidence: 99%
“…We know that CT is associated with a loss of lean mass and an increase in fat mass, independent of weight change [43]. At the same time, the reduction in lean mass is strongly associated with the important decrease in FM in our study (p = 0.0001).…”
Section: Discussionsupporting
confidence: 58%
“…In a controlled trial, 172 women with early breast cancer were randomized to consume either a diet tailored to their energy requirement for weight loss or maintenance or 2-day cycles of a fasting-mimicking diet repeated every 7 days [37]. The co-primary endpoints of changes in weight, fat mass and fat free mass did not differ between groups nor did chemotherapy toxicity differ.…”
Section: Recent Clinical Trials In Cancer Patientsmentioning
confidence: 99%